Additive manufacturing of PLA-Mg composite scaffolds for hard tissue engineering applications. (February 2023) - Bakhshi, Rasoul; Mohammadi-Zerankeshi, Meysam; Mehrabi-Dehdezi, Melika; Alizadeh, Reza; Labbaf, Sheyda; Abachi, Parvin
Abstract: Polylactic acid (PLA) is considered as a great option to be employed as 3D porous scaffold in hard tissue engineering applications owing to its excellent biocompatibility and processability. However, relatively weak mechanical properties and inappropriate biodegradability limit its extensive usage. In order to overcome the mentioned challenges, micrometric magnesium particles were incorporated into the PLA matrix by the fused deposition modeling (FDM) technique. The effects of various Mg contents (i.e., 2, 4, 6, 8 and 10 wt%) on the structural, thermal, rheological, mechanical, wettability, degradability characteristics and cellular behavior of the 3D porous PLA-Mg composite scaffolds were examined. The developed PLA-Mg composites exhibit an interconnected porous structure with a mostly uniform distribution of Mg particles in the PLA matrix. It was found that incorporation of Mg particles into the PLA matrix enhances the mechanical, physical, chemical and biological characteristics of PLA. The cell studies demonstrate that the PLA-6Mg composite scaffold provides the best cellular response in terms of cell atachment and viability. The obtained results in this investigation greatly suggest that the 3D-printed PLA-Mg composite scaffold is a promising candidate for hard tissue engineering applications. Graphical abstract: Image 1 Highlights: Incorporation of Mg particles into PLA matrix and development of porous PLA-Mg composite scaffolds with excellent resolution via FDM technique. Mg addition till 8 wt% significantly improved the mechanical properties of PLA scaffold. The low degradation rate of 3D porous PLA scaffold increased with the introduction of Mg particles. The cellular behavior of PLA-Mg composite was superior to PLA, where the PLA-6Mg scaffold demonstrated the best performance.